Long-term direct and indirect costs of ulcerative colitis in a privately-insured United States population. (2nd August 2020) - Pilon, Dominic; Ding, Zhijie; Muser, Erik; Obando, Camilo; Voelker, Jennifer; Manceur, Ameur M.; Kinkead, Frederic; Lafeuille, Marie-Hélène; Lefebvre, Patrick
Abstract: Objective: Prior evaluations of ulcerative colitis (UC)-related costs are dated or encompassed limited follow-up. This study assessed the incremental direct and indirect work loss-related costs of privately-insured patients with UC in the United States, overall and in specific subgroups. Methods: In this retrospective matched cohort study, the OptumHealth Care Solutions, Inc (formerly Optum Health Reporting and Insights employer) database (01 January 1999–31 March 2017) was used to identify adult patients with ≥2 claims for UC, who were matched 1:5 to patients with no claims for inflammatory bowel disease (IBD). UC subgroups were identified based on indicators during the observation period (i.e. use of biologics, opioids, or corticosteroids; UC-related surgery; moderate-to-severe disease; UC-related comorbidities). Healthcare resource utilization (HRU), work loss days, and direct and work loss-related costs were compared between matched cohorts. Descriptive analyses of direct and work loss-related costs were conducted within each UC subgroup. Results: Compared to the non-IBD cohort ( n  = 46, 765), the UC cohort ( n  = 9353) incurred higher HRU, including 128% more inpatients visits, resulting in $11, 029 higher direct costs per patient per year (PPPY; $7170 vs. $18, 198; p  < .001). Patients in the UC cohort also incurred more work loss days, resulting in $2142 higher work loss-related costs PPPY ($3165 vs. $5307; p  < .001). Direct and work loss-related costs were particularly high in the UC subgroups, with patients undergoing UC-related surgery incurring the highest costs. Conclusions: Over ∼5 years follow-up, patients with UC had significantly higher all-cause direct healthcare and indirect work loss-related costs compared to matched patients without IBD.